2017
DOI: 10.3892/etm.2017.4633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low dose of ethanol on the senescence score, brain function and gene expression in senescence-accelerated mice 8 (SAMP8)

Abstract: Accumulating epidemiological evidence suggests light to moderate alcohol intake reduces risk of several chronic diseases. However, there is limited information regarding the effects of low alcohol intake in animal studies. This study investigated the effect of low ethanol dosage on senescence-accelerated mouse (SAMP8), an animal model of aging and neurodegenaration. Male SAMP8 mice (11 weeks old) had free access to a commercial stock diet with drinking water containing 0, 1 or 2% (v/v) ethanol for 15 weeks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Consistent with findings from our previous study (8), the total senescence grading score in the 1% ethanol group was the lowest among the four treatment groups, whereas the scores of the 2% and 5% ethanol groups did not differ from those of the control. Furthermore, the present study revealed that, when compared against the control group, only mice given 1% ethanol had greater limb grip strength at 21 wk.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with findings from our previous study (8), the total senescence grading score in the 1% ethanol group was the lowest among the four treatment groups, whereas the scores of the 2% and 5% ethanol groups did not differ from those of the control. Furthermore, the present study revealed that, when compared against the control group, only mice given 1% ethanol had greater limb grip strength at 21 wk.…”
Section: Discussionsupporting
confidence: 91%
“…This data suggests that 1% ethanol may be favorable for senescence and muscle strength, but not 2% and 5% ethanol, thereby supporting the J-curve hypothesis of alcohol. Of note, we previously reported that 2% ethanol stimulated spontaneous locomotor movement in SAMP8 mice, but 1% ethanol did not (8); thus, the enhanced limb grip strength observed in mice given 1% ethanol is likely to be unrelated.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To the best of our knowledge, this study is the first to reveal that consumption of 0.5-1% ethanol suppresses colon tumorigenesis in DMH-treated rats, but that of 2% ethanol does not. The results are similar to those of our previous studies indicating that 1% ethanol exerted a beneficial effect on the liver function in rats fed a highfat diet (14) and on the aging process in SAMP8 mice, whereas 2% ethanol exhibited lesser effects (15). Collectively, consumption of 1% ethanol may offer health benefits, whereas that of 2% ethanol may offer lesser benefits, supporting the J-curve hypothesis for the effect of alcohol on health.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, we reported that consumption of 1% (v/v) ethanol in drinking water improved the liver function in rats fed a high-fat diet (13) and delayed the aging process in senescence-accelerated mice (SAMP8), whereas 2% (v/v) ethanol exhibited a minimal effect on the liver function and aging (14). These studies exhibit a clear beneficial effect of 1% ethanol but less so for 2% ethanol, supporting the J-curve hypothesis of alcohol consumption.…”
mentioning
confidence: 99%